Isolation and high-dimensional flow cytometric analysis of tumor-infiltrating leukocytes in a mouse model of colorectal cancer - Eich, Christina; Vogt, Johannes F.; Längst, Vivian; Clausen, Björn E.; Hövelmeyer, Nadine (Frontiers in Immunology, 2024)
Colorectal cancer (CRC) is a complex and heterogeneous disease characterized by dysregulated interactions between tumor cells and the immune system. The tumor microenvironment plays a pivotal role in cancer initiation as well as progression, with myeloid immune cells such as dendritic cell and macrophage subsets playing diverse roles in cancer immunity. On one hand, they exert anti-tumor effects, but they can also contribute to tumor growth. The AOM/DSS colitis-associated cancer mouse model has emerged as a valuable tool to investigate inflammation-driven CRC. To understand the role of different leukocyte populations in tumor development, the preparation of single cell suspensions from tumors has become standard procedure for many types of cancer in recent years. However, in the case of AOM/DSS-induced colorectal tumors, this is still challenging and rarely described. For one, to be able to properly distinguish tumor-associated immune cells, separate processing of cancerous and surrounding colon tissue is essential. In addition, cell yield, due to the low tumor mass, viability, as well as preservation of cell surface epitopes are important for successful flow cytometric profiling of tumor-infiltrating leukocytes. Here we present a fast, simple, and economical step-by-step protocol for isolating colorectal tumor-associated leukocytes from AOM/DSS-treated mice. Furthermore, we demonstrate the feasibility of this protocol for highdimensional flow cytometric identification of the different tumor-infiltrating leukocyte populations, with a specific focus on myeloid cell subsets.